2010
DOI: 10.1037/a0017225
|View full text |Cite
|
Sign up to set email alerts
|

Aging and directed forgetting in episodic memory: A meta-analysis.

Abstract: This meta-analysis examines the effects of aging on directed forgetting. A cue to forget is more effective in younger (d = 1.17) than in older adults (d = 0.81). Directed-forgetting effects were larger: (a) with the item method rather than the list method; (b) with longer presentation times; (c) with longer postcue rehearsal times; (d) with single words rather than verbal action phrases as stimuli; (e) with shorter lists; and (f) when recall rather than recognition was tested. Age effects were reliably larger … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

12
68
6

Year Published

2013
2013
2020
2020

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 63 publications
(86 citation statements)
references
References 67 publications
(125 reference statements)
12
68
6
Order By: Relevance
“…In the remember condition, subjects were told that the preceding items were the first part of the study list and should be kept in mind while studying the second part. To ensure task engagement in the critical forget condition, we used a forget instruction that provided ' Titz and Verhaeghen (2010) reported significant forgetting in older adults, with the magnitude of the effect being slightly reduced compared with young adults (p = .08). Because the analysis included the Zacks et al (1996) results, which showed reduced forgetting for older adults but suffered from a floor effect (see previous discussion), it may have overestimated the age-related difference.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…In the remember condition, subjects were told that the preceding items were the first part of the study list and should be kept in mind while studying the second part. To ensure task engagement in the critical forget condition, we used a forget instruction that provided ' Titz and Verhaeghen (2010) reported significant forgetting in older adults, with the magnitude of the effect being slightly reduced compared with young adults (p = .08). Because the analysis included the Zacks et al (1996) results, which showed reduced forgetting for older adults but suffered from a floor effect (see previous discussion), it may have overestimated the age-related difference.…”
Section: Design and Proceduresmentioning
confidence: 99%
“…[18][19][20] In the item-wise directed forgetting procedure, participants are presented with a series of words and instructed to selectively remember some studied words and forget other studied words. [21][22][23] Our rationale for using the directed forgetting procedure was to assess whether memory consolidation is driven by the selective reactivation of future-relevant memories.…”
Section: Introductionmentioning
confidence: 99%
“…However, a number of studies have provided evidence that a distinction must be made between intentional (i.e., effortful) and unintentional (i.e., automatic) inhibitory processes (Anderson, 2005;Andreś, Guerrini, Phillips, & Perfect, 2008;Conway & Fthenaki, 2003;Hogge et al, 2008). Age-related deficits are frequently observed in tasks that require intentional inhibitory processes, such as in Stroop (Hartman & Hasher, 1991;Spieler, Balota, & Faust, 1996) and directed forgetting tasks (Titz & Verhaeghen, 2010;Zacks, Radvansky, & Hasher, 1996). In contrast, a growing body of research points to the absence of age differences in tasks that tap unintentional inhibitory control (Aslan, Bauml, & Pastotter, 2007;Hogge et al, 2008).…”
Section: Retrieval-induced Forgetting Mechanismsmentioning
confidence: 96%